Literature Review: Korelasi antara Asupan Serat dan Asupan Cairan dengan Kejadian Konstipasi Fungsional pada Anak Remaja - Hosniyah Firdausiyah Safraji; Farapti Farapti (Media Gizi Kesmas, 2024)
Background: Functional constipation is a functional gastrointestinal disorder (FGID) that represents the most prevalent gastrointestinal disorder in childhood. Its reported prevalence ranges from less than 1% to 32%, varying based on the reference population and definition employed. The prevalence of functional constipation in adolescents can vary significantly in different regions of the world.  cases of functional constipation in Indonesia for ages 4 – 17 years, the prevalence of constipation was 22.6% of 482 children. When compared with other countries, functional constipation in Indonesia is relatively high. Cases of functional constipation can reduce the quality of life in the form of limited mobility, activity and productivity in teenagers. The pain experienced will really disrupt the teaching and learning process of students. Students become unfocused in studying or reduce their attendance in class because their conditions do not allow them to carry out activities as usual. Of the many factors, fiber intake and low fluid intake are the ones that cause functional constipation. Objectives: This article aims to fill the knowledge gap regarding the relationship between fiber intake and fluid intake and the incidence of functional constipation in adolescents. Methods: This study uses a literature review method from a database source, namely Google Scholar, by selecting articles published within the last 10 years, consisting of national and international articles. There were 13 articles regarding the correlation between fiber intake and fluid intake and the incidence of constipation in adolescents Results: Several articles show that low fiber intake is correlated with the occurrence of functional constipation. Adolescents who have insufficient fiber and fluid intake cause a lack of air absorption in the intestines, resulting in hard stools that are difficult to expel. Conclusion: The conclusion of the literature review emphasizes the importance of adequate fiber intake and fluid intake in preventing functional constipation in adolescents.